Accountability For The Performance Of Palembang City Government Agencies Through An Institutional Isomorphism Theory Approach - Bolley, Stevy Josephin; Desi Indriasari; Meilinda Dwi Anugrah (Jurnal Ilmiah Ekonomi Dan Bisnis, 2025)
This study identifies a research gap between the implementation of reporting systems, e-budgeting, and performance-based budgeting and The degree of accountability for performance within the Palembang City Government. Although the city has achieved a "BB" SAKIP rating, disparities remain across its agencies. The study's goal is to examine how these three factors impact performance accountability using the institutional isomorphism hypothesis.  In order to use a quantitative methodology, 94 respondents from 32 regional work units (PDs) in Palembang were given questionnaires. The findings reveal that the reporting system, e-budgeting implementation, and performance-based budgeting significantly affect accountability, both partially and simultaneously. These results support institutional isomorphism theory, which posits that coercive, normative, and mimetic pressures lead to homogenized practices within government institutions. The study concludes that improving accountability requires consistent enhancement of these three elements. It is recommended that the city government strengthen outcome-oriented planning and expand professional training across OPDs to promote greater uniformity in performance management.